PENGEMBANGAN INSTRUMEN KETERAMPILAN SOSIAL BERBASIS OBSERVASI DAN SOSIOMETRI DALAM PEMBELAJARAN IPS - Eri Purwanti; Eddy Purnomo; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2015)
The purposes of this study were to develop an instrument of social skill-based observation and sociometry and to analyze the effectiveness of the use of the instrument in grade VIII of middle school. This study was classified as Research and Development (RD) research with experimental approach. The subjects of the research consist of 2 experts of learning evaluation, 1 expert of Indonesian language, 3 students for individual evaluation, 9 students for small group evaluation, and 64 students for large group evaluation. The data were collected through observation and questionnaires and were analyzed using validity test, reliability test, and effectiveness test. The results from the research and development showed that: (1) The product produced in this study was the social skill instrument based observation and sociometry in social science learning. (2) The result of validity test revealed that the use of social skill instrument based observation and sociometry was appropriate and valid to be used for a more effective assessment.Tujuan Penelitian ini adalah mengembangkan instrumen keterampilan sosial berbasis observasi dan sosiometri dan menganalisis efektivitas penggunaan instrumen keterampilan sosial pada mata pelajaran IPS di kelas VIII SMP. Penelitian ini tergolong penelitian Research and Development (RD). Subjek uji coba melibatkan 2 orang ahli evaluasi pembelajaran, 1 orang ahli bahasa Indonesia, 3 orang siswa untuk evaluasi satu-satu, 9 orang siswa untuk evaluasi kelompok kecil, dan 64 orang siswa untuk evaluasi kelompok besar. Teknik pengumpulan data dilakukan dengan observasi dan angket. Teknik analisis data menggunakan uji validitas, reliabilitas, dan uji efektivitas. Hasil penelitian dan pengembangan yaitu: (1) Instrumen keterampilan sosial berbasis observasi dan sosiometri dalam pembelajaran IPS. (2) Hasil uji validitas menunjukan bahwa instrumen keterampilan sosial berbasis observasi dan sosiometri layak dan valid digunakan.Kata kunci: instrumen keterampilan sosial, observasi, sosiometri